2001
DOI: 10.1556/aagr.49.2001.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Supply and Sowing Date on Performance and Essential Oil Production of Anise (Pimpinella Anisum L.)

Abstract: Field and greenhouse experiments were carried out in order to determine the effects of water supply and sowing date on the performance and essential oil production of anise (Pimpinella anisum L.). The results indicated that mean leaf area (LA), specific leaf area (SLA), relative growth rate (RGR), relative water content (RWC), grain yield and essential oil decreased, while the root/shoot ratio and the oil percentage of the seeds increased when the available soil water decreased to below 80% in the greenhouse. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 1 publication
3
18
0
1
Order By: Relevance
“…(2001) show that the percentage of essential oil significantly decreases due to delayed sowing, while water deficit resulted in the increase of the essential oil content. A recent research confirms that the amount of the essential oil obtained from different species produced under drought conditions was either maintained or enhanced, depending on the extent of stress (Zehtab-Salmasi et al, 2001). Water deficit during stem elongation and umbel formation reduces anise growth, grain yield and oil production (Zehtab-Salmasi et al, 2001).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…(2001) show that the percentage of essential oil significantly decreases due to delayed sowing, while water deficit resulted in the increase of the essential oil content. A recent research confirms that the amount of the essential oil obtained from different species produced under drought conditions was either maintained or enhanced, depending on the extent of stress (Zehtab-Salmasi et al, 2001). Water deficit during stem elongation and umbel formation reduces anise growth, grain yield and oil production (Zehtab-Salmasi et al, 2001).…”
Section: Discussionmentioning
confidence: 89%
“…It can be concluded that the first part of this critical period provided favourable conditions for seed formation and filling, while the second, warmer and drier period favoured the synthesis of essential oil and fruit ripening. (Zehtab-Salmasi et al, 2001) and in investigations carried out in Turkey from 2.66 to 2.74% (Tuncturk and Yildrim, 2006). However, a higher level of anise essential oil, 3.5 to 5.5%, was observed in another experiment carried out in Iran (Omidbaigi et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been a reduction of yield in the rosemary (Rosmarinus officinalis L.) and anise (Pimpinella anisum L.) [29,36] following a water deficit, whereas in pepper (Capsicum annuum L.), the water deficit led to an increase in the essential oil yield.…”
Section: Introductionmentioning
confidence: 99%